As juventudes, lugar teológico da civilização do amor : pastoral da juventude do Maranhão e saberes da experiência - Lucas, Luisa de (2021)
This dissertation analyses the theological foundations of experiences that youth encounter as part of activities aimed at developing the mystique of the Youth Ministry. Furthermore, this paper also investigates the lifestyle of Brazilian youth, specifically, the youth of the Diocese of Caxias, Maranhão, in a social, cultural and religious context. Moreover, the research studies the lessons the young people have drown from their experiences. These outcomes have been organized according to generative themes that will be further identified as a theology produced by the lifestyle of these youth groups. Furthermore, this study addresses the place of youth within the Church. This assertion is based upon the examination of Church documents and on a systematic examination of recordings of these young people´s experiences; namely those individuals who belonged to the Pastoral da Juventude (Youth Ministry), in the JAC group (Young People Annoucing Christ) in São Domingos do Maranhão-MA from 2012 to 2018. The theological analysis of these young people´s experiences has been organized in dialogue with Pedagogical, Ethical and Anthropological approaches in the light of feminist studies. The dissertation also seeks to identify those elements which contribute to a society in which the experience of oppression and knowledge lead to a replication of a resigned youth and/or a critical youth. Finally, the study argues that young people are a “locus theologicus” for the manifestation of God - agents of evangelization for the transformation of the Church and society.